2017
DOI: 10.1002/aoc.3988
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fe3O4@5,10‐dihydropyrido[2,3‐b]quinoxaline‐7,8‐diol copper complex: A capable nanocatalyst for the green synthesis of 1‐substituted 1H‐tetrazoles

Abstract: Fe 3 O 4 magnetic nanoparticles functionalized with 5,10-dihydropyrido [2,3-b] quinoxaline-7,8-diol were synthesized as was their complex with copper as a novel nanomagnetic iron oxide catalyst via a simple and green method, and characterized using various techniques. The capability of the catalyst was evaluated in the one-pot three-component synthesis of different tetrazoles, which showed very good results. Mild reaction conditions, good reusability and simple magnetic work-up make this methodology interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 26 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Further, ICP analysis revealed that amount of Cu leaching was about 0.25 after first run and 2.5% after five consecutive runs while no leaching was observed for iron from nanocatalyst. 55 Similarly, Habibi et al also developed Fe 3 O 4 @1,10-phenanthroline-5,6-diol@Mn nano-catalyst for 1-substituted-tetrazole synthesis ( Table 3 , entry 4). 56 …”
Section: Magnetic Nano-catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%
“…Further, ICP analysis revealed that amount of Cu leaching was about 0.25 after first run and 2.5% after five consecutive runs while no leaching was observed for iron from nanocatalyst. 55 Similarly, Habibi et al also developed Fe 3 O 4 @1,10-phenanthroline-5,6-diol@Mn nano-catalyst for 1-substituted-tetrazole synthesis ( Table 3 , entry 4). 56 …”
Section: Magnetic Nano-catalyzed Synthesis Of Tetrazolesmentioning
confidence: 99%
“…The reaction conditions appear quite compatible with the canons of Green Chemistry, since they were carried out in H 2 O or ethanol as the solvent, under microwave irradiation for very short durations (10-18 min). Copper(II) complexed to an Fe3O4-functionalized 5,10-dihydropyrido[2,3-b] quinoxaline-7,8-diol ligand was instead developed in 2018 by Habibi and co-workers for the synthesis of 1-substituted 1H-tetrazoles by a one-pot, three-component reaction of anilines with sodium azide and triethylorthoformate [183]. Such a catalyst, named Fe3O4@Quinindiol@Cu by the authors, worked well with anilines bearing both electron-donating (-CH3, -OCH3) or electron-withdrawing functional groups (-Cl, -Br, -NO2, -COCH3, -CF3), affording the desired N-heterocycles in high yields.…”
Section: Metal Catalysts Supported On Metal Oxides or Minerals-anchor...mentioning
confidence: 99%
“…Immobilization of Pd(II)-polysalophen on the magnetite provides a cohesive lattice structure with a high surface-to-volume ratio (according to the proposed structure for the catalyst in Scheme 4) that causes the compounds to penetrate into the catalyst structure in an aqueous medium, and aer the reaction, they are separated from the surface of the catalyst, in full agreement with the suggested mechanisms that water has been used as a solvent in the organic reactions. [41][42][43][44] In order to investigate this phenomenon, in another control test, the catalytic activity of a physical mixture of Pd(II)-polysalophen and Fe 3 O 4 @SiO 2 was studied (Table 5, entry 6).…”
Section: Control Experimentsmentioning
confidence: 99%